Penerapan Literasi Digital dalam Pembelajaran IPS di Masa Pandemi Covid-19 - Widiati, Tia; Ruhimat, Mamat (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2022)
This research is motivated by the Covid-19 pandemic which requires learning to be carried out online. Social studies learning, which is known to have a lot of memorization, requires social studies teachers to creatively prepare good lesson plans. One of the most effective ways to support social studies learning is by implementing digital literacy. Digital literacy is one of the skills that can support the achievement of the right education to support learning that applies 21st century skills. The method used is a one shot case study design pre-experimental method. This study involved social studies teachers and junior high school students. The implemented digital literacy includes Social Science learning materials for grade VII junior high school. In conclusion, the implementation of digital literacy in social studies learning during the Covid-19 pandemic is suitable to be applied to class VII students, because of students' difficulties in memorizing social studies material through the use of digital literacy. Abstrak Penelitian ini dilatarbelakangi oleh pandemi Covid-19 yang mengharuskan pembelajaran dilaksanakan secara daring. Pembelajaran IPS yang dikenal banyak hafalan mengharuskan guru IPS dengan kreatif menyusun rencana pembelajaran yang baik. Salah satu cara paling efektif untuk menunjang pembelajaran IPS dengan menerapkan literasi digital. Literasi Digital merupakan salah satu keterampilan yang dapat mendukung tercapainya pendidikan yang tepat untuk menunjang pada pembelajaran yang menerapkan keterampilan abad-21. Metode yang digunakan adalah metode pre-eksperimen desain one shot case study. Penelitian ini melibatkan guru IPS dan siswa sekolah menengah pertama. Literasi digital yang dipenerapankan memuat materi pembelajaran Ilmu Pengetahuan Sosial kelas VII sekolah menengah pertama. Kesimpulannya, penerapan literasi digital dalam pembelajaran IPS pada masa pandemi Covid-19 ini cocok diterapkan pada siswa kelas VII, karena kesulitan siswa dalam mengahafal materi IPS melalui pemanfaatan literasi digital.